Studi Pencemaran Pabrik Briket Batu Bara - D Karyadi (Jurnal Kimia dan Kemasan, 1997)
Coal brequet are hoped to replace the earth oil fuel and wood that nowadays have been critically supplying and limited usage. The operational activities which can caused pollution are the supplying of raw materials and additives, production process and post production. Therefore we sugest to maintain a good management for operational activities, especially to minimize pollution.